Regulatory considerations for developing phage therapy medicinal products for the treatment of antimicrobial resistant bacterial infections - Fukaya-Shiba, Ai; Ogata, Akiko; Kuribayashi, Ryosuke; Sakurai, Akira; Suzuki, Kanako; Takadama, Shunsuke; Nishimura, Jihei; Uchiyama, Jumpei; Ohge, Hiroki; Takeuchi, Takamasa; Tamaki, Hideyuki; Matsumoto, Tetsuya; et al. (Frontiers in Pharmacology, 2025)
Recently, there have been growing expectations that treatment of infections with bacteriophages (phages), viruses which specifically infect bacteria, can be used as a treatment option for antimicrobial resistant bacterial infections. In Europe and the United States, in addition to phage therapy as a form of personalized medicine, development of pre-defined phage therapy medicinal products (PTMPs) is progressing, and clinical trials are underway. From October 2024 to July 2025, the Pharmaceuticals and Medical Devices Agency exchanged opinions on trends and points to consider in drug development of PTMPs used for antimicrobial resistant bacterial infections with external experts. Development of PTMPs for regulatory approval requires quality control strategies, establishment of manufacturing methods, non-clinical evaluations, and clinical trial plans based on the characteristics of the phage. In this document, based on the regulatory and development trends in Europe and the United States, the current considerations on quality, non-clinical evaluation, and clinical trial planning including the Cartagena Act in the development of PTMPs in Japan are summarized. The basic concepts presented here are intended to be applied to antimicrobial resistant bacterial infections targeted by PTMPs but can be mostly applicable to bacterial infections in general. We hope that these findings will further accelerate more active development of PTMPs towards timely patient access to innovative products.